Characterization of dairy farms using humid citrus husks for ruminant feeding - Mart?nez, J.; Hern?ndez, N.; Jord?n, Humberto; Chongo, Bertha; Torres, Verena; Fontes, Dayam?; Lezcano, Yohanka; Cubillas, Nieves (Cuban Journal of Agricultural Science, 2010)
The amount of animals, the farm areas, the social aspects, and the variables related to the use of humid citrus husks were selected to characterize the dairy farms using humid citrus husks for ruminant feeding. The data were obtained through surveys and informal interviews. In order to measure the effect of the utilization of the citrus husks, a methodology was applied using multivariate techniques. Out of the analysis, different groups were formed. Four principal components were obtained explaining 84.3 % of the variance: 1) amount of feeds, 2) information on the use of citrus husks for cattle feeding, 3) availability of industrial wastes, and 4) management of the animals. The forage area variable was outstanding within the principal component 1, which accounted for 30.9 % of the total variance of the system. It was observed that the groups use the citrus husks not taking into account the capacity of these systems to generate forages. The general trend was to use the citrus husk without nitrogen source. The small proportions of biomass banks were noteworthy. It was concluded that the amount of feeds in the forage area had great importance in the differentiation of the farms, which led to the high dependence by the citrus husk in the dry season. The farmers had little knowledge on the nutritive characteristics of the citrus husks, and kept the access of the animals to the byproduct in a restricted form in most of the groups because the available amount was not enough. Key words: dairy farms, citrus husk, feeding.